A Multicenter Qualitative Investigation of the Experiences and Perspectives of Substitute Decision Makers Who Underwent Organ Donation Decisions. (December 2018) - Sarti, Aimee J.; Sutherland, Stephanie; Healey, Andrew; Dhanani, Sonny; Landriault, Angele; Fothergill-Bourbonnais, Frances; Hartwick, Michael; Beitel, Janice; Oczkowski, Simon; Cardinal, Pierre
Background: Organ donation research has centered on improving donation rates rather than focusing on the experience and impact on substitute decision makers. The purpose of this study was to document donor and nondonor family experiences, as well as lasting impacts of donation. Methods: We used a qualitative exploratory design. Semistructured interviews of 27 next-of-kin decision makers were conducted, transcribed verbatim, and entered into qualitative software. We analyzed the process-based reflections using inductive coding and thematic analysis techniques. Results: Four broad and interrelated themes emerged from the data: empathetic care, information needs, donation decision, and impact and follow-up. The donation experience left lasting impacts on family members due to lingering, unanswered questions. Suggested solutions to improve the donor experience for families included providers employing multimodal communication, ensuring a proper setting for family meetings, and the presence of a support person. Discussion: We now have improved our understanding of the donation process from the perspective of and final impression from the next of kin. To our knowledge, this is the largest cohort interviewed in Canada. We have explored families' experiences, which included but did not end with donation. We learned that despite being appreciative of nurses, physicians, and organ and tissue donation coordinators, family members were often troubled by unanswered questions. Conclusion: This study described donor and nondonor family experiences with donation as well as lasting impacts. Addressing unanswered questions should be done in a place sufficiently remote from the donation event to enhance the family members' understanding and well-being.